Characterization of molecularly imprinted polymer (MIP) for an extraction Of curcumin from Curcuma longa (Turmeric) - Emi Shaqiza, Azizi
A molecularly imprinted polymer (MIP) for selective extraction of curcumin has been synthesized via non-covalent approach by using curcumin as a template. Polymerization was prepared using 2 (two) functional monomers namely methacrylic acid (MAA) and acrylamide (AM) together with 3 (three) different porogens namely chloroform (CHCl3), tetrahydrofuran (THF) and acetonitrile (MeCN). Porosity and surface area analysis revealed that the polymer prepared using THF as porogen has the highest average pore diameter size i.e. 618.43 nm. Batch binding analysis revealed that the largest imprinting factor was attained by the polymer prepared using MAA and THF as functional monomer and porogen respectively. Further characterization was carried out using 3 (three) isotherm models namely Langmuir (LI), Freundlich (FI) and Langmuir-Freundlich (LF-I) isotherm. The unknown parameters in each isotherm were calculated by using Solver function in Microsoft Excel and were optimized for R2 value. The calculated R2 values were found to be (0.91), (0.69) and (0.96) for LI , FI and LFI respectively.. Hence, LFI was further used to calculate the binding sites (N) and homogeneity (m) of both the MIP and NIP (non-imprinted polymer). The result showed that MIP1 has more Nt (1250.62 µg/g) as compared to NIP ( 998.35 πg/g) suggesting that MIP has more binding sites and selective towards curcumin. A 150 mg of polymer mass was packed into SPE (solid phase extraction) cartridge and subsequently used to extract curcumin from raw turmeric extract. The recoveries were 43.10% for MIP as compared to 13.46% for NIP. This suggested that the MIP cartridge exhibited significant selectivity toward curcumin, with recoveries 67.76% and 39.86% for NIP, indicating that the synthesized MIP has the potential for curcumin purification through SPE.